PENANGANAN KONFLIK AGRARIA DI DESA TUMANG KECAMATAN SIAK KABUPATEN SIAK TAHUN 2012-2014 - Rio Ranzani Saputra; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Tumang Village is one of village in subdistrict Siak, Siak regency. In administration, the village is included in subdistrict Siak region. But ironically, people who have been long livead an remained there not recognized property rights over their land. Community rights as a citizen plagued by the company PT. Seraya Suumber Lestari because the company has permission obbtained from the foresty minister namely foresty ministerial decree number SK.22/MENHUT-II/2007.The research problem are what the cause of agrarian conflict in Tumang Villages? And what the government efforts Siak regency in dealing agrarian conflict. The purpose of this research is to know what the cause of agrarian conflict in Tumang Villages and to know what the government efforts Siak regency in dealing agrarian conflict.The location of this research is in The Tumang Village. The method used is qualitative. Data collection techniques with interview. Concucted to determine how conflict can occur and how did the conflict resolution. Literature study is a way of collecting data.Based on the research result conflict in The Tumang Village is starting from the company license (IUPHHK-HTI) given by minister of forestry. The expenditur procces without involving public. So that people demand their rights az citizen of Indonesia. This is one of the causes conflict. Furthermore, the efforts made by government Siak iis acceptance of complaints, research, prevention of mutation, mediation, discussion and through courts. However, all efforts have not done well. So get less than optimal result.Key word: handling, agrarian, agrarian conflict.